Systematic Review Of Management Of Janu Sandhigata Vata (Knee Osteo Arthritis) Through Ayurveda (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Janu sandhigata vata or ostoe arthritis of knee is a chronic degenerative disease which comes in humen being by age. the main symptoms of this disease are pain , stiffness , difficulty in walking and it affects daily routine work of life. Ayurveda and panchakarma treatment is very effective and popular management of this disease. Considering the higher incidence of this disease due to various faulty lifestyles and Vatik Ahara vihara, it is necessary to elaborate on safe and effective management in Ayurveda sciences.The present study has done a systematic review of effectiveness and safety of Sodhana and shamana treatment in Janu Sandhigata Vata (Osteo-arthrits of Knee). The information relevant to the study is compiled from previous research studies, i.e. Clinical trials, randomized or not having interventions of various panchakarma modalities and published in various peer reviewed journals and also available on multiple databases such as Pubmed, google scholars, ShodhaGanga, Cochrene library etc. till August 2022 irrespective of their study centre. Abhyanga (Massage), Swedana karma (Sudations procedures) and Basti Karma (enema therapy ) used as single treatment or combined treatment protocol with other Ayurvedic treatment modules showed benefit in osteoarthritis of knee . Future studies on the long-term efficacy and safety goals aligned to psychosomatic record of patients are required for personalized Ayurveda multimodal care. Aim and objectivesAim: this systemic review study is Basically planned to review previous conducted clinical researches based on the type of intervention i.e. Various panchakarma interventions used for management of Janu Sandhigata Vata and to make its specific treatment protocol.Objective: to assess the efficacy and safety of panchakarma Procedures in management of Janu Sandhigata Vata .Material and methodology: The information relevant to the study is compiled from previous research studies, i.e. Clinical trials, randomized or not having interventions of various panchakarma modalities and published in various peer reviewed journals and also available on multiple databases such as Pubmed, google scholars, ShodhaGanga, Cochrene library etc. till August 2022 irrespective of their study centre. References of key articles were hand searched using the keywords such as ‘Janu Sandhivata ’, ‘Janusandhigata Vata’‘Panchakarma’, ‘Shodhana’, ‘ Matra Basti’, ‘Snehapana ’, ‘JanuDhara’, ‘Upnaha’etc. Database of CTRI was also searched with the same keywords to get a list of current and completes researches on Janusandhigata Vata.Only those manuscripts which were published in English language were eligible for inclusion. Screening of both the title and abstract and full text of the retrieved articles were conducted independently by two reviewers and a third reviewer resolved any disagreement. A narrative synthesis of the characteristics of study participants and types of intervention with specific outcomes are mentioned.Study selectionInclusion criteria: Data-analysis was focused entirely on only ayurvedic controlled clinical trials (randomized And non-randomized controlled trials conducted in patients suffering with Janu Sandhigata Vata till August 2022.Exclusion criteria: Ayurvedic review articles on Janu Sandhigata Vata Ayurvedic clinical studies conducted on complications of Janu Sandhigata Vata , related animal studies, case study or case series, observational study& modern sciences studies and researches were excluded from the study.Assessment parameters: These studies were assessed based on the inclusion & exclusion criteria, type of methodology, assessment parameters, type of intervention used (Shodhana or Panchakarma, Shamana management or their combination) and its outcomes measures reported.Observations and results: A total of 53 articles were retrieved after searching the selected database i.e.Pubmed, web of science, Shodhaganga, Medknow, google scholars and CTRI using a comprehensive search strategy. Out of 53 manuscripts 13 were removed as they were literature review. Full text 40 research papers were identified but amongst them, 17 were excluded as they did not match the methodology.This systematic review is based on information from a total 23 interventional studies by critically analysing them to verify the necessity and assess the role of panchakarma chikitsa.